2016
DOI: 10.1186/s40064-016-1778-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an HPLC method for the determination of vancomycin in human plasma and its comparison with an immunoassay (PETINIA)

Abstract: Vancomycin (VAN) is among those antibiotics for which therapeutic drug monitoring is highly recommended. For this purpose a reliable method with small sample volume was required for quantification of VAN in human plasma. Therefore, a selective and sensitive method of high performance liquid chromatography was developed and validated. The separation was carried out isocratically by using a mobile phase NH4H2PO4 (50 mM, pH 2.2)–acetonitrile (88:12, v/v) at a flow rate of 0.36 mL/min on a nucleodur C18 column (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 32 publications
0
30
2
2
Order By: Relevance
“…It was found that the IC 50 value was 13.74 ng/L, the IC 20 -IC 80 were 3.43-43.62 ng/L, and the IC 10 reached up to 1.07 ng/L according to the established IC-TRFIA for Van. The LOD value was 1.07 ng/L in the presented IC-TRFIA for Van, which is more sensitive (approximately 60-fold) compared with Kong et al (2017) established IC-ELISA for Van with LOD value of 0.06 ng/mL, and approximately 460-fold, 2.0 × 10 5 -fold and 2.5 × 10 5 -fold compare with Liang et al (2015), Sheng and Zhou (2017) and Usman and Hempel (2016) which were established fluorescence "turn-off" biosensor, two-dimensional liquid chromatography and HPLC for Van with LOD value of 0.46 ng/mL, 0.2 and 0.25 μg/mL respectively. In addition, it was slightly better than Liu, Yan, Hua, and Wang (2013), Hu et al (2018), Zhou et al (2015) and Sheng et al (2016) established IC-TRFIAs for thiacloprid, aflatoxin B 1 , chloramphenicol and diniconazole with LOD value of 1.9, 3.55, 8.0 and 21 ng/L, respectively.…”
Section: Ic-trfia Establishment Of Van and Its Analoguesmentioning
confidence: 79%
“…It was found that the IC 50 value was 13.74 ng/L, the IC 20 -IC 80 were 3.43-43.62 ng/L, and the IC 10 reached up to 1.07 ng/L according to the established IC-TRFIA for Van. The LOD value was 1.07 ng/L in the presented IC-TRFIA for Van, which is more sensitive (approximately 60-fold) compared with Kong et al (2017) established IC-ELISA for Van with LOD value of 0.06 ng/mL, and approximately 460-fold, 2.0 × 10 5 -fold and 2.5 × 10 5 -fold compare with Liang et al (2015), Sheng and Zhou (2017) and Usman and Hempel (2016) which were established fluorescence "turn-off" biosensor, two-dimensional liquid chromatography and HPLC for Van with LOD value of 0.46 ng/mL, 0.2 and 0.25 μg/mL respectively. In addition, it was slightly better than Liu, Yan, Hua, and Wang (2013), Hu et al (2018), Zhou et al (2015) and Sheng et al (2016) established IC-TRFIAs for thiacloprid, aflatoxin B 1 , chloramphenicol and diniconazole with LOD value of 1.9, 3.55, 8.0 and 21 ng/L, respectively.…”
Section: Ic-trfia Establishment Of Van and Its Analoguesmentioning
confidence: 79%
“…Thus, it is clinically necessary to monitor VAN blood concentration. Monitoring methods mainly include high-performance liquid chromatography, radioimmunoassay, and enzyme amplification immunoassay [8]. Since VAN is a time-dependent antibacterial drug, the key to ensuring its efficacy is extending the antibacterial drug infusion time such that the drug concentration is always higher than the target organism's minimum inhibitory concentration [9].…”
mentioning
confidence: 99%
“…HPLC is a type of chromatographic separation technique that is commonly coupled with UV, [55][56][57] (photo)diode array (DA), [58][59] fluorescence, 60 mass spectrometry (MS) 51,[61][62][63] or electrochemical 64 detector for the identification and quantification of the analyte(s) of interest. Due to its high sensitivity and specificity, HPLC has been considered the gold standard for Van quantification among the different analytical methods.…”
Section: Hplcmentioning
confidence: 99%
“…58 Especially in complicated biological fluids, HPLC proves to be an accurate and reliable tool to detect Van at concentrations below the therapeutic range which are often unattainable by immunoassays. [55][56] Another advantage of HPLC over immunoassays is the ability to isolate and quantify the degraded products of Van. [55][56] Furthermore, a simultaneous detection of Van and other commonly co-prescribed antibiotics has been performed on HPLC systems which improves the efficiency of analysis.…”
Section: Hplcmentioning
confidence: 99%
See 1 more Smart Citation